Prospecção Química e Biológica de Fungos Endofíticos associados à Aniba rosaeodora (Lauraceae) - Silva, Celina de Jesus (2010)
Endophytic fungi are microorganisms that live inside plants without causing apparent damage. The result of this mutual relationship can justify the production of important compounds to the biotechnology. As an example of an Amazon native tree, Aniba rosaeodora is producer of essential oil rich in linalool, a secondary metabolite of great commercial interest. Considering the literature, that report the capacity of endophytic fungi to produce, in vitro, metabolites identical to them of the host plant, the study with endophytic fungi becomes a viable alternative to search for a new source for production of linalool and other compounds that may have relevant activity. Were isolated 262 fungi from four specimens of A. rosaeodora. These fungi were subjected to fermentation and after fourteen days, the supernatants were analyzed in the chromatograph high performance liquid chromatography (HPLC), resulting in ten samples with chromatograms with different profile to each other and seventeen samples suggested the presence of linalool . These samples were fractionated and sent for analysis by a gas chromatography coupled to mass spectrometer (GC/MS). Seven samples showed a spectrum with the fragmentation profile similar to the profile of linalool standard, which suggests the production of this compound by endophytic fungi. They also observed the formation of supernatants other substances, such as farnesol, citronellol, undecane, phenethyl alcohol, among others. To evaluate the antibacterial and antifungal activity of supernatants of fungi with the codes PRII-Fo 68 and PRII-Ca 256 showed inhibitory activity for the growth of Pseudomonas aeruginosa, with average inhibition zones of 26 mm and 10 mm in diameter, respectively, and extracts of the mycelium of the fungi with the codes PRIII-Fo 134 and PRIII-Fo 136 showed inhibitory activity for the growth of Penicillium avelani, with average inhibition zones of 23 mm and 28 mm in diameter, respectively. Was done on a large scale culture of the 51 fungus with code PRII-Fo 68 and the supernatant was submitted to a liquid-liquid partition resulting in extracts of different polarities. These results suggest good prospects for a possible new source of linalool, and other substances that may be useful in biotechnology. A sustainable way to guard the plant species (A. rosaeodora) the risk of extinction.